2019
DOI: 10.1075/itl.17026.app
|View full text |Cite
|
Sign up to set email alerts
|

Lexical aspects of comprehensibility and nativeness from the perspective of native-speaking English raters

Abstract: This study analyzed the contribution of lexical factors to native-speaking raters’ assessments of comprehensibility and nativeness in second language (L2) speech. Using transcribed samples to reduce non-lexical sources of bias, 10 naïve L1 English raters evaluated speech samples from 97 L2 English learners across two tasks (picture description and TOEFL integrated). Subsequently, the 194 transcripts were analyzed through statistical software (e.g., Coh-metrix, VocabProfile) for 29 variables spanning various le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 43 publications
(40 reference statements)
1
20
0
Order By: Relevance
“…Following this line of thought, Appel et al. (2019) stressed the importance of evaluating the accurate use of lexicogrammar from the perspective of comprehensibility (i.e., overall ease of understanding). Therefore, the same two expert L1 Vietnamese raters also conducted the lexicogrammar judgments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this line of thought, Appel et al. (2019) stressed the importance of evaluating the accurate use of lexicogrammar from the perspective of comprehensibility (i.e., overall ease of understanding). Therefore, the same two expert L1 Vietnamese raters also conducted the lexicogrammar judgments.…”
Section: Methodsmentioning
confidence: 99%
“…Even if two individuals of the same age and with similar levels of motivation engage in the same type of practice for the same period of time, they will most likely end up with different levels of proficiency (Doughty, 2019). Part of this variation can be attributed to learner‐internal abilities related to perception and general cognition (e.g., Linck et al., 2013, for working memory, and see Appel, Trofimovich, Saito, Isaacs, & Webb, 2019, for a special issue on the topic covering a range of learner‐internal individual differences). These abilities are thought to be instrumental in the acquisition of relatively difficult, complex, and nonsalient linguistic features because they can help learners better encode, analyze, memorize, and internalize the input that they receive (Li, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in comprehensibility research, native-speaking listeners are typically recruited to listen to and rate the comprehensibility of speech samples produced by L2 users with various proficiency levels. Previous research has shown that listeners likely attend to particular linguistic features to grasp the overall message of the samples, including segmental contrasts with high functional load and several minimal pairs (e.g., Munro & Derwing, 2006; Suzukida & Saito, in press), prosodic accuracy and fluency (e.g., Kang, Rubin, & Pickering, 2010), and lexical appropriateness and complexity (e.g., Appel, Trofimovich, Saito, Isaacs, & Webb, 2019; Saito, Webb, Trofimovich, & Issacs, 2016). The features that factor most heavily into judgments are known to differ according to a number of variables such as the proficiency level of speakers in the samples (low- vs. mid- vs. high-level comprehensibility) (Saito, Trofimovich, & Isaacs, 2016) and the type of speaking task (interview vs. picture descriptions) (Crowther, Trofimovich, Isaacs, & Saito, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Lexicogrammatical, such as grammatical accuracy, as mentioned by Munro and Derwing (1995); Saito, Webb, Trofimovich, and Isaacs (2016b); Varonis and Gass (1982); 4. Lexical richness/appropriateness, as noted by Appel, Trofimovich, Saito, Isaacs & Webb (2019); Fayer and Krasinski (1987); Saito et al (2016bSaito et al ( , 2017; and 5. Segmental features, as identified by Derwing and Munro (1997), Isaacs and Trofimovich (2012), Munro and Derwing (1995), Saito et al (2017); Trofimovich and Isaacs (2012).…”
Section: Background 1 Second Language Comprehensibilitymentioning
confidence: 94%